Addressing avoidable vision impairment in Mozambique and the Africa region. Issue 2 (17th February 2019) - Thompson, Stephen; Naidoo, Kovin; Bambamba, Joel; Moodley, Vanessa; van Staden, Diane; Forde, Amanda; Shah, Kajal; Bilotto, Luigi; Loughman, James
ABSTRACT: The Mozambique Eyecare Project was an international partnership to implement and research eye health education in Mozambique and the Africa region. An optometry degree was developed at Universidade Lúrio, Mozambique. In addition, existing eye health workers were upskilled with training. Researchers from various disciplines evaluated the project and its potential for impact on eye health in the region. The body of evidence generated from the research provides useful lessons for development programmes in general, as well as specific lessons for delivering eye health education and service delivery models for low-income settings.